Analysis of soft gelatin capsule with real-time polymerase chain reaction for halal autenthication - Nina Salamah; Any Guntarti; Laela Hayu Nurani (Pharmaciana, 2023)
Halal medicine is an interesting topic to always discuss because it is a priority choice for Muslim consumers, one of which is halal capsules. Currently, molecular biology techniques such as real-time polymerase chain reactions are rapidly developing, including for the analysis of non-halal components based on DNA sequences. This study aimed to validate the quantitative PCR method for identifying DNA in gelatin-based products and to apply the confirmation method designed for capsule samples on the market circulating in Yogyakarta to prove the halalness of these samples. Validation of the porcine DNA detection analysis method on standard extraction of porcine gelatin using primer pairs obtained in previous studies. Validated methods are used for testing market capsule shells. The qPCR method using D-loop primers is specifically capable of amplifying porcine gelatin DNA up to a concentration of 0.5 pg/µL, with a CV value in the amplification response of porcine gelatin DNA isolates (1000 pg/µL) of 0.85% which meets the test criteria using the PCR. Three samples of commercial soft capsules tested gave a positive amplification response, meaning that the samples tested contained porcine DNA, and one negative sample, which probably had non-porcine gelatin. The application of this method is also very useful for ensuring the authenticity of the capsule shell, especially from cross-contamination and counterfeiting.